1988
DOI: 10.1073/pnas.85.15.5688
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay for octapeptide analogs of somatostatin: measurement of serum levels after administration of long-acting microcapsule formulations.

Abstract: The development of a long-acting delivery system for D-Phe-Cys-Tyr-D-Trp-Lys-Val-Cys-Trp-NH2 (RC-160), an octapeptide analog of somatostatin, required the establishment of a method for determining the concentration of this analog in serum during treatment. A sensitive and specific radioimmunoassay (RIA) for RC-160 was developed and used for following the rate of liberation of this peptide from microcapsules of poly(DL-lactide-coglycolide). Antibodies were generated in a rabbit against RC-160 coinugated to bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 16 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…The synthetic SV 1 -hapten was conjugated to fatty acid-free BSA (Sigma) with glutaraldehyde (Sigma) as reported in ref. 30. The SV 1 -hapten-BSA complex was freshly prepared each time.…”
Section: Methodsmentioning
confidence: 99%
“…The synthetic SV 1 -hapten was conjugated to fatty acid-free BSA (Sigma) with glutaraldehyde (Sigma) as reported in ref. 30. The SV 1 -hapten-BSA complex was freshly prepared each time.…”
Section: Methodsmentioning
confidence: 99%
“…However, the duration of release appeared longer with the SB-75 pamoate microgranules. Previously, we showed that the pamoate salt of the somatostatin analog RC-160 in microcapsule formulations exhibited a protracted release as compared with the acetate form (8). Because the primary high release from the microcapsules and/or microgranules ensures a rapid elevated level of antagonist, the initial "burst effect" can be beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…13 In addition to the variability within the assay, cross-reactivity existed for peptide structurally similar to RC-160. MasonGarcia et al, 14 for instance, reported 15% cross-reactivity between octreotide and RC-160.…”
Section: Radioimmunoassay Binding Curvementioning
confidence: 99%